Potential of plant beneficial bacteria and arbuscular mycorrhizal fungi in phytoremediation of metal-contaminated saline soils - Ma, Ying (2020)
Phytoremediation has been considered as a promising technique to decontaminate polluted soils. However, climatic stress particularly salinity, is a potential threat to soil properties and plant growth, thus restricting the employment of this technology. The aim of this study was to access the impact of microbial inoculation on phytoremediation of nickel (Ni) contaminated saline soils using Helianthus annuus. Salt resistant plant beneficial bacterium (PBB) Pseudomonas libanensis TR1 and arbuscular mycorrhizal fungus (AMF) Claroideoglomus claroideum BEG210 were used. Inoculation of P. libanensis alone or in combination with C. claroideum significantly enhanced plant growth, changed physiological status (e.g. electrolyte leakage, chlorophyll, proline and malondialdehyde contents) as well as Ni and sodium (Na+) accumulation potential (e.g. uptake and translocation factor of Ni and Na+) of H. annuus under Ni and salinity stress either alone or in combination. These results revealed that bioaugmentation of microbial strains may serve as a preferred strategy for improving phytoremediation of metal-polluted saline soils.